Computational Docking Study of Oxazepine Based Compounds as Inhibitors of Acetylcholinesterase Enzyme in Alzheimer’s Disease - Addanki, Aneesha; Nadendla, Rama Rao; Kanakaraju, Vijaya Kishore (International Journal of Pharmaceutical Investigation, 2025)
Background Alzheimer's disease has become a serious health problem in recent years. Certain acetylcholinesterase inhibitors have been shown to have anti-Alzheimer's properties. In the current work, a number of oxazepine compounds were developed and docked against acetylcholinesterase (PDB ID: 7e3h) in order to investigate such activity. The ligands and conventional acetylcholinesterase inhibitors were contrasted. Materials and Methods The ligands were sketched in .mol format using ChemSketch and then converted to .pdb format using Avogadro. The iGEMDOCK software was used for molecular docking investigations and Discovery Studio Visualizer was used to display the results. Results and Discussion Most of the compounds showed improved binding affinities for acetylcholinesterase enzyme. Compared to common acetylcholinesterase inhibitors like galantamine (-102.1 kcal/mol) and rivastigmine (-91.8 kcal/mol), all of the ligands demonstrated lower binding energies. For visualization, the top two compounds, 8d (-109.2 kcal/mol) and 9c (-102.6 kcal/mol), were selected. Conclusion Oxazepine derivatives show promise as an anti-Alzheimer's disease treatment. Because compared to conventional antagonists, they have a higher binding affinity to the acetylcholine esterase enzyme.
Keywords: Oxazepine derivatives; Acetylcholine esterase; Anti-Alzheimer’s; Molecular Docking; iGEMDOCK Software and Discovery Studio Visualizer